2014
DOI: 10.1111/adb.12157
|View full text |Cite
|
Sign up to set email alerts
|

MT‐7716, a potent NOP receptor agonist, preferentially reduces ethanol seeking and reinforcement in post‐dependent rats

Abstract: Dysregulation of the nociceptin (N/OFQ) system has been implicated in alcohol abuse and alcoholism and growing evidence suggests that targeting this system may be beneficial for treating alcoholism. To further explore the treatment target potential of the N/OFQ system, the novel non-peptide, small-molecule N/OFQ (NOP) agonist MT-7716, (R)-2-{3-[1-(Acenaphthen-1-yl)piperidin-4-yl]-2-oxo-2,3-dihydro-1H-benzimidazol-1-yl}-N-methylacetamide hydrochloride hydrate, was examined for its effects on ethanol self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 39 publications
6
49
0
Order By: Relevance
“…This is consistent with a NOP receptor agonist-induced decrease in extracellular dopamine in the NAc (Murphy et al, 1996;Vazquez-DeRose et al, 2013). Nevertheless, the ability of NOP receptor agonists to block self-administration of these drugs appears to be far less robust, if effective at all (Walker et al, 1998;Ciccocioppo et al, 2014;de Guglielmo et al, 2015). One difference in the way in which NOP receptor agonists have been tested in these two "drug abuse" paradigms is that NOP receptor agonists block acquisition of CPP but generally have been tested for their ability to block expression of selfadministration.…”
Section: Future Directions and New Toolssupporting
confidence: 75%
See 1 more Smart Citation
“…This is consistent with a NOP receptor agonist-induced decrease in extracellular dopamine in the NAc (Murphy et al, 1996;Vazquez-DeRose et al, 2013). Nevertheless, the ability of NOP receptor agonists to block self-administration of these drugs appears to be far less robust, if effective at all (Walker et al, 1998;Ciccocioppo et al, 2014;de Guglielmo et al, 2015). One difference in the way in which NOP receptor agonists have been tested in these two "drug abuse" paradigms is that NOP receptor agonists block acquisition of CPP but generally have been tested for their ability to block expression of selfadministration.…”
Section: Future Directions and New Toolssupporting
confidence: 75%
“…N/OFQ and the selective small molecule agonist Ro 64-6198 have both been demonstrated to block ethanol selfadministration in rats (Ciccocioppo et al, 1999(Ciccocioppo et al, , 2004Kuzmin et al, 2007); however, these studies have been generally conducted in alcohol preferring rat strains, some of which, including the Marchigian Sardinian alcohol preferring rat line, showed anomalies in their NOP-N/OFQ system (Economidou et al, 2008). Other studies found NOP agonists to be effective in decreasing alcohol drinking only in rats with a previous history of alcohol dependence but not in unselected or nondependent rat lines de Guglielmo et al, 2015). A single publication found efficacy in normal Wistar rats (Kuzmin et al, 2007).…”
Section: Biologic Actions Of Nociceptin Opioid Peptide Receptorsmentioning
confidence: 99%
“…These rats showed that NPS specifically exerts anxiolytic effects on msP rats. A similar phenomenon was previously observed for drugs such as nociception agonists and CRF1 receptor antagonists; both classes of compounds possess marked anxiolytic effects and reduced alcohol drinking in msP rats but not in heterogeneous Wistar rats (Ayanwuyi et al 2013; Ciccocioppo et al 2014; de Guglielmo et al 2015; Gehlert et al 2007). Most importantly, our finding agrees with previous studies published in genetically selected alcohol-preferring P rats, in which ICV administration of NPS attenuated home cage alcohol drinking and elicited a marked anxiolytic effect (Badia-Elder et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…In these rats, NOP agonists attenuate home cage alcohol drinking, operant alcohol self-administration, and drug seeking elicited by stress and environmental conditioning factors (Ciccocioppo et al, 2004;Economidou et al, 2006aEconomidou et al, , 2008. The efficacy of NOP agonists on alcohol intake has also been documented in post-dependent outbred Wistar rats whereas they are not effective in nondependent Wistar rats, unless very high doses are used (de Guglielmo et al, 2015a;Economidou et al, 2006a;Kuzmin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%